Vila Galé hotels' internationalization to Cape Verde - Teixeira, Inês dos Santos Ângelo Neves (2015)
The intent of this paper is to assess the most suitable internationalization strategy for Vila Galé Hotels into the Cape Verdean market (namely into Sal Island), under an investment on a 5-star resort with an all-inclusive system. First, the company’s historic moves onto opening new business units, its corporate strategy triangle and its brand communication channels were studied. Afterwards, the macroeconomics, the hotel industry and other relevant trends of the country at stake were analysed in order to understand the best positioning for Vila Galé in the market as well as the most fitting plan for the project. Finally, it was shown that building a 5-star resort is the most appropriate mode of entry into this market. Keywords: